2017
DOI: 10.31234/osf.io/psh48
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is automatic speech-to-text transcription ready for use in psychological experiments?

Abstract: Verbal responses are a convenient and naturalistic way for participants to provide data in psychological experiments (Salzinger, 1959). However, audio recordings of verbal responses typically require additional processing such as transcribing the recordings into text, as compared with other behavioral response modalities (e.g. typed responses, button presses, etc.). Further, the transcription process is often tedious and time-intensive, requiring human listeners to manually examine each moment of recorded spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Instead, we intend to provide a proof-of-concept that an ASR can be used to analyze certain aspects of spontaneous speech, allowing for large-scale use of natural speech for research ends. A similar approach has recently been taken by Ziman et al (2018), who showed that an ASR can be used reliably to transcribe speech data from psychological experiments, in their case a verbal recall memory test. In their study, Ziman and colleagues provided the speech context to their speech-to-text engine.…”
Section: Using Spontaneous Speech Elicitation and Asr In Individual Dmentioning
confidence: 96%
See 1 more Smart Citation
“…Instead, we intend to provide a proof-of-concept that an ASR can be used to analyze certain aspects of spontaneous speech, allowing for large-scale use of natural speech for research ends. A similar approach has recently been taken by Ziman et al (2018), who showed that an ASR can be used reliably to transcribe speech data from psychological experiments, in their case a verbal recall memory test. In their study, Ziman and colleagues provided the speech context to their speech-to-text engine.…”
Section: Using Spontaneous Speech Elicitation and Asr In Individual Dmentioning
confidence: 96%
“…The strength of the correlations might be considered an index of how well a given measure, in the context of spontaneous speech elicitation, is suited to be transcribed by an ASR, or whether it may require manual coding. (For a similar correlational approach to evaluate transcription accuracy, see Ziman et al, 2018. ) As we planned to carry out correlations for many measures of interest, we applied a Bonferroni correction (four measures and three questions resulted in a corrected alpha level of 0.05/12 = 0.004).…”
Section: Asr Accuracymentioning
confidence: 99%
“…The word lists participants studied were drawn from the categorized lists reported by Ziman et al (2018). Each participant was assigned four unique randomly chosen lists (in a randomized order), selected from a full set of 16 lists.…”
Section: Survey Questionsmentioning
confidence: 99%
“…This could be addressed by telephone contact, but one unexpected outcome of using instant messaging was the active use by some patients of session transcripts as personalised psychoeducation materials. This benefit would be lost, although the latest advances in voice recognition and automatic transcription may eventually render this issue obsolete [20,25,81]. Access to transcripts may be particularly helpful for patients who do not engage with formal worksheets and could be actively encouraged by therapists in such situations.…”
Section: The Choice Of Communications Modesmentioning
confidence: 99%